Techno-economic analysis of a two-step fermentation process for bio-butanol production from cooked rice - Ozturk, Abdullah Bilal; Arasoglu, Tulin; Gulen, Jale; Cheng, Shou; Al-Shorgani, Najeeb Kaid Nasser; Habaki, Hiroaki; Egashira, Ryuichi; Kalil, Mohd Sahaid; Yusoff, Wan Mohtar Wan; Cross, Jeffrey Scott (ROYAL SOC CHEMISTRY, 2021)
The food wastage problem and its associated issues have become a significant threat to sustainable development, particularly in developing countries. Cooked rice, which has been reported to be one of the most abundant regional food wastes, is a substantial feedstock for biofuel production due to its rich carbon content. In this study, both solid-state and acetone-butanol-ethanol (ABE) fermentations were conducted in series with Aspergillus oryzae and aero-tolerant Clostridium acetobutylicum YM1 for the biobutanol production. To validate the process parameters for an industrial-scale process, it is critical to examine the effects of process parameters using a process simulation tool. To this end, by adapting lab-scale process results, a techno-economic evaluation of the biobutanol production from the cooked rice by two-step fermentation was performed using SuperPro Designer (R). This study aims to examine various scenarios for cooked rice utilization to produce butanol while examining process optimization and minimization of operational expenses for the aerobic ABE fermentation and microbial saccharification. According to the simulation results, butanol production cost was estimated to be 1.24 $ kg(-1), incorporating a cost reduction of 0.58 $ kg(-1) from heat integration, steam and power generation, while eliminating costs for the unnecessary commercial enzymes and N-2 gas for purging. Finally, sensitivity analysis was applied to demonstrate the plant feasibility concerning potential fluctuations in the changing biofuel market and environmental conditions.
Keywords: MUNICIPAL SOLID-WASTE; CLOSTRIDIUM-ACETOBUTYLICUM; BIOBUTANOL PRODUCTION; FOOD WASTE; ABE FERMENTATION; WHEAT-STRAW; ENZYMATIC-HYDROLYSIS; ECONOMIC-EVALUATION; ETHANOL-PRODUCTION; ACID; Chemistry; Energy & Fuels; Materials Science